Emergency Stenting of Tandem Stenoses of the Internal Carotid Artery Using Proximal Protection Against Distal Embolism “MoMa” - E. Yu. Kachesov; A. N. Kazantsev; A. V. Bykovsky; A. V. Korotkykh (Неотложная медицинская помощь)
Man, 61 years old. Admitted with complaints of severe weakness in the right limbs, which developed about 4 hours ago. Multispiral computed tomography with cerebral angiography: signs of ischemic stroke in the basin of the left middle cerebral artery. Angiography of the brachiocephalic arteries (BCA) was performed: angiographic signs of damage to the BCA: the left internal carotid artery (ICA) of the C2–C3 segments up to subocclusion, up to 75% in the mouth and right third. The circle of Willis is closed.A multidisciplinary council made a decision on emergency stenting of tandem ICA stenoses using proximal protection against distal embolism “MoMa”. The course of the operation: after angiography, the sheath introducer was replaced by a guidewire sheath with a 9F introducer. A proximal protection system “MoMa” was installed along the diagnostic conductor 260 cm at the mouth of the left external carotid artery (ECA) and the middle third of the left common carotid artery (OCA). Baloons in the ECA and OCA were inflated. The Promus element 4.0x12 mm (DES) ICA was brought into the affected area of C2–C3 segments, positioned and opened at a pressure of up to 14 atm. The balloon catheter has been removed. Aspiration from the ICA. On check angiography, residual stenosis of the ICA stenting zone was 0%. On the test angiography intracranial arteries without signs of embolism. A Protege (7x10x40) mm stent was placed, positioned and deployed in the affected area of the orifice and the right third of the ICA. The delivery system has been removed. Aspiration from the ICA. On the test angiography, the residual stenosis of the ICA stenting zone was up to 0%. The distal embolism protection system has been removed. On the control angiography intracranial arteries without signs of embolism.The postoperative period was uneventful. On the 10th day after stenting, the neurological deficit regressed completely, the patient was discharged for outpatient observation in a satisfactory condition.CONCLUSIONS When performing brain revascularization in the most acute period of ischemic stroke, it is necessary to take into account the recommendations of multicenter studies that report such conditions for a successful outcome of the operation as: the diameter of the ischemic focus in the brain, not exceeding 2.5 cm and the absence of severe neurological deficit (more than the Rankin scale score 2). Within the framework of this clinical example, these recommendations were taken into account, which, among other things, contributed to the optimal outcome of urgent revascularization. Emergency stenting of tandem stenosis of the internal carotid artery using the device for proximal protection “MoMa” is effective in the presence of a closed structure of the circle of Willis. The technical complexity of the operation is associated with the installation of a catheter guide and its diameter of 9 Fr (catheters up to 7 Fr are usually used), which requires additional manual skills.